2004
DOI: 10.1590/s0074-02762004000400011
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Calomys callosus (Rodentia Cricetidae) with strains of different Trypanosoma cruzi biodemes: pathogenicity, histotropism, and fibrosis induction

Abstract: The influence of different Trypanosoma cruzi biodemes on the evolution of the infection and on the histopathological lesions of the heart and skeletal muscles, during the experimental infection of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
(7 reference statements)
0
6
1
Order By: Relevance
“…Indeed, binding between extracellular matrix proteins and T. cruzi receptors has been described as a significant step in this phenomenon (Santana et al ., 1997). It is important to report that Magalhães‐Santos et al (2004), working with Calomys callosus , did not observe an increase of collagen deposits in damaged tissues.…”
mentioning
confidence: 95%
“…Indeed, binding between extracellular matrix proteins and T. cruzi receptors has been described as a significant step in this phenomenon (Santana et al ., 1997). It is important to report that Magalhães‐Santos et al (2004), working with Calomys callosus , did not observe an increase of collagen deposits in damaged tissues.…”
mentioning
confidence: 95%
“…It involves parasitized macrophages, cardiac and skeletal muscles cells in different animal species such as mice, dogs, and Callomys callosus (Andrade 1991, Cordeiro et al 1997, Magalhães-Santos et al 2004. In acute Chagas' disease in humans, necrosis of cardiac myocells, either containing intracellular forms of T. cruzi or in the absence of parasites, constitutes an outstanding feature in advanced acute chagasic myocarditis (Andrade 1991).…”
mentioning
confidence: 99%
“…The various clinical manifestations that occur throughout the development of Chagas’ disease are directly related to the genotype of the circulating parasites, the geographic origin and the cycles of wild and domestic transmission. This is because these variations in the populations determine the tropism to the tissues, the parasitaemia, and the pathogenesis in the vertebrate hosts during the acute and chronic phase of the disease (Andrade et al ., 1999; Macedo et al ., 2004; Magalhães-Santos et al ., 2004). In our review, we observed that, after 50 inoculations with more than 20 different T. cruzi strains, those belonging to the TcI (ex Colombian), TcII (ex Y) (Galea et al , 2007) and TcIV (ex AM05) (Meza et al ., 2014) were those that presented histotropism for the CNS.…”
Section: Discussionmentioning
confidence: 99%